A CRITICAL DISCOURSE ANALYSIS OF SEXISM IN “BRAVE” MOVIE - Robiatul Adawiyah; Elisa Nurul Laili (Kampus Akademik Publiser, 2024)
Abstract This study focused on describing the sexist language and social structure through movie “ BRAVE